Clinical case of co-infection: Dengue fever and respiratory mycoplasmosis in a child - D.V. Preobrazhenskaia; E.V. Melekhina; Zh.B. Ponezheva (Respiratory Medicine Case Reports)
According to WHO, dengue fever (DF) is currently endemic to more than 100 countries in various regions of Africa, America, and Asia; outbreaks have been reported in Europe. In the Russian Federation, there is a much smaller proportion of children among those infected due to the imported nature of the infection.We described a clinical case of imported dengue fever in an adolescent girl in Moscow after a 5-day vacation. Despite the fact that during the examination at the hospital in the Maldives, DENV arbovirus antigen was isolated in the blood by immunochromatographic rapid test, the course of the disease had a number of symptoms that did not conform to the classical course of the disease: catarrhal symptoms, cough, elevated C-reactive protein, and radiographic evidences of right-sided maxillary sinusitis. No improvement in the condition was observed despite the therapy administered. Additional examination confirmed an active infection caused by M. pneumoniae. After correction of etiotropic and pathogenetic therapy, the patient was discharged with recovery on day 10 of the disease.After 4 years since the start of the pandemic, an increase in infectious morbidity, particularly DF, has been observed. The proportion of co-infections is increasing. Co-infection of DF and respiratory mycoplasmosis in children may occur masked as an acute respiratory viral infection (ARVI): with intensification of catarrhal and intoxication syndromes and atypical changes in laboratory parameters. All that complicates clinical and laboratory diagnosis and leads to incorrect administration of starting etiotropic therapy.